2017
DOI: 10.1007/978-3-319-66095-0_13
|View full text |Cite
|
Sign up to set email alerts
|

The Current Role of Cell-Penetrating Peptides in Cancer Therapy

Abstract: Cell-penetrating peptides (CPPs) are a heterogeneous class of peptides with the ability to translocate across the plasma membrane and to carry attached cargos inside the cell. Two main entry pathways are discussed, as direct translocation and endocytosis , whereas the latter is often favored when bulky cargos are added to the CPP. Attachment to the CPP can be achieved by means of covalent coupling or non-covalent complex formation, depending on the chemical nature of the cargo. Owing to their striking abilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 104 publications
0
38
0
Order By: Relevance
“…Therefore, out of necessity, the authors chose to provide only a very broad overview of classification, mechanism of transduction and highlight applications of CPPs as vectors for gene and nucleic acid delivery only. Readers are referred to an earlier review of CPPs by the authors [8] as well as several other excellent reviews [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, out of necessity, the authors chose to provide only a very broad overview of classification, mechanism of transduction and highlight applications of CPPs as vectors for gene and nucleic acid delivery only. Readers are referred to an earlier review of CPPs by the authors [8] as well as several other excellent reviews [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…CPPs can be attached to the nanocarrier surface conferring the potential to translocate across the membrane via micropinocytosis. 126,127 CPPs are normally short peptides of 1 to 5 kDa of less than 20 basic amino acids and can be attached to >30 kDa cargoes (eg, TAT). 128 CPP-based drug strategies are considered a form of subcellular targeting due to preferential accumulation in the cell nuclei and sub-nuclear regions.…”
Section: Lectinsmentioning
confidence: 99%
“…The ionic structure composition of poly(lysine) peptides may thus diminish its propensity to bind and penetrate cell membranes. However, secondary structure studies of poly(lysine) by electronic and vibrational CD spectroscopy revealed helixto-coil transitions, that were dependent on temperature, solvent, additives and sample concentrations (Drake et al, 1988;Xia and Li, 2011). The apparent helical conformations were characterized as either a left-handed α-helix or a polyproline type II helix which primarily governed the most dominant peptide secondary structure motifs.…”
Section: Poly(lysine)mentioning
confidence: 99%
“…More specifically, CPPs and CTPs are about 4-30 amino acids in length, derived from biologically active motifs found in proteins or from selection techniques that have ushered in unique peptides with the abilities to target cell surface biological markers (e.g., cell surface receptors) and translocate within cells by a variety of cell uptake mechanisms (Habault and Poyet, 2019). As such, CTPs and CPPs have been applied to transport various cargos such as nucleic acids (McClorey and Banerjee, 2018), proteins (Kristensen et al, 2016), imaging probes (Juliano et al, 2009), and drugs (Feni and Neundorf, 2017) into selected cell lines for activity.…”
Section: Introductionmentioning
confidence: 99%